P09.23 High prevalence of hiv infection among patients with sti syndromes in zimbabwe: implications for prevention. (13th September 2015) - Mungati, M; Machiha, A; Tshimanga, M; Gonese, E; Nyakura, J; Kilmarx, P; Shambira, G; Kupara, V; Herman-Roloff, A; Nichol, A; Handsfield, H; Rietmeijer, C
Abstract : Introduction: The occurrence of sexually transmitted infection (STI) syndromes among persons with HIV infection indicates the presence of high-risk behaviours and biological co-factors favouring HIV transmission. We determined HIV prevalence among patients enrolled in a study of the aetiology of STI syndromes in Zimbabwe. Methods: In an ongoing study, we enrolled men and women with genital discharge syndrome (GDS) or genital ulcer disease (GUD) at 6 geographically diverse clinics in Zimbabwe. We used Xpert® CT/NG to determine the presence of Neisseria gonorrhoeae (NG) and Chlamydia trachomatis (CT) in urethral or vaginal specimens from all study participants. Blood samples were collected for HIV testing by a standard rapid HIV test algorithm (First Response™ followed by Alere HIV 1/2™) and considered positive when reactive on both. Blood samples were also tested for treponemal antibodies (SD Bioline HIV/syphilis DUO™). Results: To date we completed laboratory test on 371 patients. Of these, 150 (40.4%) were HIV-infected. HIV rates were as follows. Female GUD: 35/62 (56.5%) vs. female GDS: 46/116 (39.7%, p = 0.05) and male GUD: 32/72 (44.4%) vs. male GDS (37/121 (30.6%, p < 0.05). HIV-infected GDS/GUD patients were significantly more likely to have positive treponemal tests compared to HIV uninfected (10.3% vs. 4.8%; p < 0.05). They were also more likely to test positive for NG (40.0% vs. 29.4%; p = 0.07), but less likely to test positive for CT (12.2% vs. 20.3%; p = 0.07). Conclusion: In our study, HIV prevalence was high among patients with STI syndromes and higher among patients with GUD than patients with GDS. The high prevalence of NG infections and evidence for recent syphilis infection among persons with documented HIV infection indicates high risk behaviours related to HIV acquisition and/or ongoing HIV transmission. Clinics serving patients with STI syndromes in Zimbabwe and countries with similar HIV/STI epidemiology are of continued importance in HIV diagnosis and prevention.